2023
DOI: 10.21203/rs.3.rs-2501091/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Occludin regulates HIV-1 infection by modulation of the interferon stimulated OAS gene family

Abstract: HIV-1-associated blood brain barrier (BBB) alterations and neurocognitive disorders are frequent clinical manifestations in HIV-1 infected patients. The BBB is formed by cells of the neurovascular unit (NVU) and sealed together by tight junction (TJ) proteins, such as occludin (ocln). Pericytes are a key cell type of NVU that can harbor HIV-1 infection via a mechanism that is regulated, at least in part, by ocln. After viral infection, the immune system starts the production of interferons, which induce the ex… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 119 publications
0
1
0
Order By: Relevance
“…Reports from our laboratory 25,31,33,35,36, including data presented in Fig 2I , have shown that ocln can regulate the extent of HIV-1 infection in various cell types, including brain pericytes. However, no studies have been performed in vivo demonstrating the influence of ocln on HIV replication in the brain.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Reports from our laboratory 25,31,33,35,36, including data presented in Fig 2I , have shown that ocln can regulate the extent of HIV-1 infection in various cell types, including brain pericytes. However, no studies have been performed in vivo demonstrating the influence of ocln on HIV replication in the brain.…”
Section: Resultsmentioning
confidence: 94%
“…Recently, our laboratory demonstrated that the ISG family 2’,5’-oligoadenylate synthetases (OAS) genes can regulate HIV-1 replication in BBB pericytes. However, the specific role of ISGs in HIV infection of this cell type remains largely unknown 25.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humanized mice, HIV-infected T cells and macrophages migrate from the periphery to the brain, potentially establishing an HIV reservoir at this site [63]. Indeed, HIV may infect several cell types within the CNS, including, astrocytes [64], pericytes [65] and myeloid-resident cells, such as microglia and perivascular macrophages [66].…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…Furthermore, it is worth noting that occludins, as guardians of skin barrier function, may extend beyond their role in preserving skin integrity. Recent research suggests that occludins may be part of a complex network involved in metabolic regulation, impacting intercellular connections [82]. While the direct influence of occludins on metabolism remains a subject of debate, there are indications that they may play significant roles in intercellular signaling and metabolic pathways [83].…”
Section: Occludins and Barrier Functionmentioning
confidence: 99%